Supervision of the School Principle in Improving the Performance of High School Teachers in Bandar Lampung - Saputra, Angga; Darmawan, Oki; Amiruddin, Amiruddin (Universitas Sang Bumi Ruwa Jurai, 2023)
The principal is responsible for the successful implementation of education by carrying out school administration with all of its substance, besides that the principal is responsible for the quality of existing resources so that they are able to carry out their duties in accordance with their respective duties and functions. Therefore, the purpose of this research is to 1) find out the initial preparation, planning, implementation, and evaluation of supervision by the principal in improving the performance of high school teachers in Bandar Lampung; and 2) Knowing the obstacles and solutions to the implementation of high school teacher supervision in Bandar Lampung. This research is a field research with a qualitative approach. The research was conducted at SMAN 2 Bandar Lampung and SMA Al-Azhar 3 Bandar Lampung. The principal acts as research informant, while the vice principal, teachers and staff act as research subjects. Data collection techniques using interviews, observation, and documentation. The data analysis process is based on the Miles qnd Hubberman model with 4 stages, namely Data Collection, Data Reduction, Data Presentation, and Conclusion Drawing. Data verification uses source triangulation and methodological triangulation techniques. Based on the results of the research, the clinical supervision program at SMAN 2 Bandar Lampung and SMA Al-Azhar 3 Bandar Lampung has been implemented properly, the principal has made plans, compiled programs and implemented clinical supervision programs. The program planned by the school principal in carrying out clinical supervision is weekly, monthly and semesterly.